A beginner's guide to macromolecular crystallization. (3rd February 2021) - Gorrec, Fabrice
Abstract : Obtaining diffraction-quality crystals is currently the rate-limiting step in macromolecular X-ray crystallography of proteins, DNA, RNA or their complexes, in the vast majority of cases. Since each sample has different and specific characteristics – which is the reason for wanting to study every single one of them in the first place – crystallization conditions cannot be predicted. Hence, researchers must enable crystal nucleation and growth through experimentation and screening. The size, shape and surface of the sample or complexes of interest are often altered through genetic and biochemical manipulation to facilitate crystallization, based on bioinformatics analyses and trial and error. Pure samples are trialled against a very broad range of crystallization conditions. The currently predominant method to achieve crystallization is sitting drop vapour diffusion with nanolitre-class robotic liquid handlers. Once initial screening yields crystals, further optimization experiments are usually required to obtain larger and diffraction-quality crystals.